Effects of contextual socioeconomic stressors on adolescents: mediation and moderation by marital and parent-child relationships - Jung, Tony Easter (2007)
This study presents different methods of longitudinal data analysis used to model continuity and change in family research. Innovative modeling techniques such as auto-regressive models, cross-lagged models, latent growth curves, interlocking growth trajectories, latent class growth analysis, and general mixture modeling are used to model the mechanisms in the family stress model. According to the family stress paradigm, negative stressors such as economic stress, work-related stress, and negative life events lead to poor mental health in parents, negatively impact the marital relationship, and undermine effective parenting. In turn, poor parental mental health, marital distress, and ineffective parenting are expected to have a cumulative negative impact on adolescent well-being. The purpose of this study is to explore the mechanisms through which contextual socioeconomic stressors may negatively impact parental and adolescent mental health and undermine effective parenting skills among single-parent mothers. It was expected that the negative effects of these distal stressors on children are mediated through their parents. In addition, this study investigates the possible role of spousal support from the single-mothers' former spouse as moderator of these contextual stressors. Specifically, it was expected that a positive relationship with the former spouse will significantly buffer the effects of these negative stressors on parenting and on the mental health of the single mothers and their adolescent children. The implications of such findings would be that the benefits of positive spousal support may not be limited to married couples. Rather, divorced parents may also benefit from receiving support from their former spouses, particularly in the form of supportive parenting. Hence, the long-term outlook on the well-being and parenting effectiveness of divorced single-parents does not necessarily have to be as bleak as many make it out to be